Experimental and numerical analysis of tube-core claddings under blast loads - Theobald, M.D.; Nurick, G.N. (International journal of impact engineering, 2010)
An investigation into the response of a sandwich cladding panel under blast loading is presented. The sandwich cores are composed of square thin-walled metallic tubes. Three primary panel layouts are identified, consisting of panels with four, five and nine tubes within the core. Annealed mild steel and 6063-T6 aluminium alloy tubes are selected as the core material. Hemispherical indentation triggers are used to induce progressive, symmetric buckling. A series of experimental blast tests are conducted on the proposed panels. A ballistic pendulum is used to measure the impulse transferred to the panel. At smaller blast impulses, irregular buckling modes are observed for both the steel and aluminium tube-core panels primarily due to variable trigger performance. For blasts which utilize the full stroke of the tubes, symmetric buckling modes are observed. In all cases panel crush distance increases with increasing impulse and decreases with an increasing number of tubes in the panel core. Further to this, at equal charge mass, the aluminium tube cores show significantly higher crush distance than identical steel tube panels. Analytical predictions of panel response give satisfactory agreement with experimental and finite-element results provided the response is within the pre-compaction regime. Finite-element results using ABAQUS/Explicit also show satisfactory correlation with experimentally obtained global response. Numerical analysis shows that energy absorption is primarily confined to the core tubes with only minimal plastic strains developing in the top plate. A numerical parametric study is conducted to determine influence of load uniformity on panel response. Energy absorption efficiency is found to be highly sensitive to the uniformity of the load, primarily in panels with fewer core tubes and thinner top plates.